Designing Educational Systems to Illustrate Mechatronic Principles - Šitum, Željko; Drašković, Tomislav; Hruškar, Fran; Meštrić, Lovro; Šego, Mateo; Stemberger, Eros; Antolković, Magdalena (International Conference Fluid Power 2025: Conference Proceedings, 2025)
This article presents six innovative laboratory mechatronic systems developed as educational prototypes to illustrate fundamental mechatronic principles to engineering students. The first prototype is an oncooscillator that generates oscillating magnetic fields via a rotating magnet driven by a DC motor, potentially demonstrating biomedical applications such as tumour cell disruption. The second is a robotic fire-fighting system ("firebot") connected to a water tanker for fire suppression. The third prototype models a cargo transport vehicle facing challenges of load instability on uneven terrain. The fourth is a mini-vessel equipped with a gyroscopic stabilization mechanism to minimize lateral rolling during navigation. The fifth is an automated chessboard capable of autonomous gameplay, piece movement, and board state recognition. The final system is a compact underwater vehicle (submarine) designed for submerged exploration and operational tasks. These prototypes serve as practical tools for bridging theoretical knowledge with hands-on learning in mechatronics education.